Socket Migration for OpenMosix - Bowker, Ethan (Kansas State University, 2008)
Process migration is a technique in clustering and distributed computing by which parallel applications can be dynamically moved between nodes in a cluster in response to differing phases of execution, which is of growing usefulness in the field of distributed computing. A drawback to many recent implementations of process migration is that sockets for interprocess communication do not migrate with the process requiring communication to be rerouted through the process' starting, or home, node, resulting in reduced communications performance when the process is migrated away from its home node. This thesis focuses on the implemention a solution to this problem at the kernel level for the OpenMosix process migration system with efficient socket handoff and cluster-wide unique addressing by reimplemting TCP on top of the existing network code in the Linux kernel. Although falling short of the initial goal of fully transparent operation, this thesis presents a working implementation of migratable sockets for the OpenMosix process migration system that demonstrates working socket migration and improved performance over non-migrating sockets in OpenMosix.
Keywords: Sockets; Clustering; Computer Science (0984)